Early-strength, high-strength and self-expanding sleeve grouting material and preparation method thereof
By using components such as magnesium oxide, magnesium sulfate, metakaolin and whisker inducers in the grouting material, early strength, high strength and self-expanding sleeve grouting materials were prepared, which solved the problem of insufficient strength in the early and later stages of the existing grouting materials, and achieved efficient component connection and excellent structural performance.
Patent Information
- Application Number
- CN202410568981.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-09
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-05-09
AI Technical Summary
The existing grouting materials have shortcomings in early and later strength. The condensation speed is too fast or too slow, and the flowability is greatly lost, making it difficult to meet the high-performance needs of prefabricated building components connections.
The components such as magnesium oxide, magnesium sulfate, metakaolin and whisker inducers (such as sodium laurate, lauric acid, potassium monosilicate) are used to prepare early-strength, high-strength and self-expanding sleeve grouting materials by controlling the component ratio and mixing process to inhibit the formation of Mg(OH)2, promote the formation of alkaline magnesium sulfate whiskers, and improve the early and later performance of grouting materials.
The excellent early strength performance of the grouting material is achieved, the compressive strength reaches the standard of ultra-high strength sleeve grouting material, and at the same time it has appropriate self-expansion performance and moderate settling time to meet the requirements of construction efficiency and structural performance.
Smart Images

Figure BDA0004830279730000041 
Figure BDA0004830279730000051 
Figure BDA0004830279730000052
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of grouting materials, and more specifically, to an early-strength, high-strength and self-expanding sleeve grouting material and a preparation method thereof. Background Art
[0002] Prefabricated building structures have the advantages of high efficiency, low energy consumption and environmental protection. In order to improve the integrity of prefabricated building structures, it is necessary to connect the various scattered components. Therefore, the key point of the integrity technology of prefabricated building structures is the connection between the components. There are two main traditional connection methods: welding and bolt connection. Since stress deformation can easily lead to cracks, it cannot be disassembled after welding, which is not easy to repair and inflexible. Bolt connection will cause the overall weight and cost of prefabricated buildings to be large, and it is easy to fail due to excessive force. Therefore, the steel sleeve connection technology is currently the commonly used technology for component connection in prefabricated buildings. The steel sleeve connection technology has the advantages of excellent performance, low cost, reduced deadweight, and convenient construction. It is the main guarantee of the integrity and seismic performance of prefabricated structures. The performance of the sleeve grouting material is the key technology of steel sleeve connection. Its performance plays a vital role in structural safety and durability.
[0003] In the connection of prefabricated building components, traditional grouting materials have many challenges, so the development of high-performance sleeve grouting materials has become one of the important measures to achieve the industrialization of construction. The classification and main problems of grouting materials currently on the market and used in engineering are as follows:
[0004] (1) Grouting materials with sulphoaluminate cement as the main cementing material have high early strength, but they will have problems such as too fast setting speed, short construction operation time, and large loss of fluidity over time.
[0005] (2) The biggest problem with grouting materials that use ordinary Portland cement as the main binder is that they set slowly, shrink during the later hardening process, and affect the construction progress and quality. The application of this type of grouting material in projects that require early strength will be limited.
[0006] In summary, it is necessary to develop a new type of early-strength self-expanding sleeve grouting material with high early strength, high late strength, moderate setting time and micro-expansion. Summary of the invention
[0007] The present application provides an early-strength, high-strength and self-expanding sleeve grouting material and a preparation method thereof. The grouting material of the present application has excellent early-strength performance, and the compressive strength reaches the standard of ultra-high-strength sleeve grouting material. At the same time, it has suitable self-expanding performance and moderate setting time.
[0008] In the first aspect, the present application provides an early-strength, high-strength and self-expanding sleeve grouting material, which adopts the following technical solution:
[0009] An early strength, high strength and self-expanding sleeve grouting material comprises the following components by weight: 250-330 parts of magnesium oxide, 87-175 parts of magnesium sulfate, 25-33 parts of metakaolin, 1.25-1.65 parts of whisker inducer, and 120-150 parts of water; the whisker inducer is at least one of sodium laurate, lauric acid, and potassium laurate.
[0010] By adopting the above technical solution, based on the formula of the present application, when magnesium oxide meets water, [(MgOH)(H2O)] will be formed on the surface of MgO. + Octahedron. In the MgO-MgSO4-H2O system, the whisker inducer will be adsorbed on the MgO surface after deprotonation. The carboxyl oxygen of the whisker inducer reacts with [(MgOH)(H2O)] + The formation of these chelates limits the [(MgOH)(H2O)] + and OH - The reaction of Mg(OH)2 inhibits the formation of Mg(OH)2, reduces its influence on the formation of basic magnesium sulfate whiskers and the influence on the strength of the grouting material. Therefore, the present application can reduce the content of magnesium hydroxide to a very small amount, reducing the negative impact of magnesium hydroxide.
[0011] At the same time, with the formation of magnesium ion chelate, small intermediates characterized by layered sandwich structures begin to form. In this process, SO4 2- and Mg 2+ It can enter the gap structure of the intermediate. When SO4 2- and Mg 2+ When the concentration reaches a certain level, magnesium sulfate whiskers gradually begin to form. As the hydration time increases, a large number of water molecules and SO4 2- The tetrahedrons are embedded in the crystals due to their attraction to the crystal lattice. This results in the formation of a large number of magnesium sulfate whiskers through self-assembly. Magnesium sulfate whiskers can effectively improve the early and late performance of sleeve grouting materials.
[0012] The whisker inducing agent of the present application will also leave a proper amount of MgOH2 in the process of inhibiting the generation of MgOH2, which will excite the metakaolin to generate hydrated magnesium aluminum gel and hydrotalcite. In addition, a proper amount of MgOH2 makes the grouting material have a suitable expansion property.
[0013] In summary, the grouting material of the present application has excellent early strength performance, and the compressive strength reaches the standard of ultra-high strength sleeve grouting material. At the same time, it has suitable self-expansion performance, does not crack due to excessive expansion, and has moderate setting time.
[0014] Further, an early strength, high strength and self-expanding sleeve grouting material comprises the following components by weight: 300-330 parts of magnesium oxide, 87-120 parts of magnesium sulfate, 30 parts of metakaolin, 1.50-1.65 parts of whisker inducer, and 120-150 parts of water. Further preferably, the grouting material comprises the following components by weight: 300-parts of magnesium oxide, 120 parts of magnesium sulfate, 30 parts of metakaolin, 1.55 parts of whisker inducer, and 135 parts of water.
[0015] Further, the magnesium oxide is a powder with a particle size between 20 and 80 microns. Further, the magnesium sulfate is a powder with a particle size between 20 and 80 microns. Further, the metakaolin is a powder with a particle size between 20 and 80 microns.
[0016] In the second aspect, the present application provides a method for preparing an early-strength, high-strength and self-expanding sleeve grouting material, which adopts the following technical solution:
[0017] A method for preparing an early-strength, high-strength and self-expanding sleeve grouting material comprises the following steps:
[0018] The magnesium oxide, magnesium sulfate, whisker inducer, metakaolin and water are mixed to prepare a slurry with good fluidity to obtain a grouting material.
[0019] In summary, this application has the following beneficial effects:
[0020] 1. The early-strength self-expanding sleeve grouting material developed in this application has the following obvious advantages: (1) Early strength: After 1 day of curing, its compressive strength can reach about 40MPa; after 3 days of curing, the compressive strength can reach 80% of the 28-day strength. (2) High strength: After 28 days of curing, the compressive strength exceeds 120MPa, which is an ultra-high-strength sleeve grouting material. (3) Self-expansion: Traditional sleeve grouting materials will shrink, which leads to poor performance of sleeve components; the grouting material of this application has a micro-expansion property, resulting in strong bonding between the sleeve and the grouting material. (4) Moderate setting time: 1 hour for initial setting and 5 hours for final setting; fully meets construction requirements and improves construction efficiency.
[0021] 2. The use of the whisker inducer with specific components in the present application inhibits the large-scale generation of MgOH2, which is not only conducive to the formation of beneficial basic magnesium sulfate whiskers, but also improves the early and late performance of the sleeve grouting material. Moreover, the whisker inducer of the present application controls the residual amount of MgOH2 within a suitable range, and these MgOH2 will excite the metakaolin and help the grouting material to have suitable expansion properties. DETAILED DESCRIPTION
[0022] The present application is further described in detail below with reference to the embodiments.
[0023] Example
[0024] The present embodiment provides an early strength, high strength and self-expanding sleeve grouting material, which comprises the following components by weight: 250-330 parts of magnesium oxide, 87-175 parts of magnesium sulfate, 25-33 parts of metakaolin, 1.25-1.65 parts of whisker inducer, and 120-150 parts of water.
[0025] Wherein, the whisker inducing agent is at least one of sodium laurate, lauric acid and potassium laurate.
[0026] Magnesium oxide is a powder with a particle size between 20 and 80 microns. Magnesium sulfate is a powder with a particle size between 20 and 80 microns. Metakaolin is a powder with a particle size between 20 and 80 microns.
[0027] This embodiment also provides a method for preparing an early-strength, high-strength and self-expanding sleeve grouting material, comprising the following steps:
[0028] The magnesium oxide, magnesium sulfate, whisker inducer, metakaolin and water are mixed to prepare a slurry with good fluidity to obtain a grouting material.
[0029] Unless otherwise specified, the raw materials used in this application can be obtained commercially.
[0030] The following is an explanation through specific examples.
[0031] Example 1
[0032] Example 1 provides an early strength, high strength and self-expanding sleeve grouting material, which comprises the following components by weight: 300 parts of magnesium oxide, 120 parts of magnesium sulfate, 30 parts of metakaolin, 1.25 parts of whisker inducer, and 135 parts of water. The whisker inducer is sodium laurate.
[0033] Embodiment 1 also provides a method for preparing an early-strength, high-strength and self-expanding sleeve grouting material, comprising the following steps:
[0034] The magnesium oxide, magnesium sulfate, whisker inducer, metakaolin and water are mixed to prepare a slurry with good fluidity to obtain a grouting material.
[0035] Example 2-11
[0036] The difference between Example 2-11 and Example 1 is that the contents of the components in the grouting material are different, as shown in Table 1 for details.
[0037] Table 1 Grouting material raw material ratio table of embodiment 1-11
[0038]
[0039]
[0040] Example 12
[0041] Example 12 provides an early strength, high strength and self-expanding sleeve grouting material comprising the following components by weight: 300 parts of magnesium oxide, 120 parts of magnesium sulfate, 30 parts of metakaolin, 1.55 parts of whisker inducer, and 120 parts of water. The whisker inducer is lauric acid.
[0042] Embodiment 13
[0043] Example 13 provides an early strength, high strength and self-expanding sleeve grouting material comprising the following components by weight: 300 parts of magnesium oxide, 120 parts of magnesium sulfate, 30 parts of metakaolin, 1.55 parts of whisker inducer, and 150 parts of water. The whisker inducer is potassium laurate.
[0044] Comparative Example
[0045] Comparative Example 1
[0046] Comparative Example 1 provides a grouting material, the raw materials of which include the following components: 450 parts of silicate cement grouting material with a model number of #525 and 135 parts of water. The raw materials are mixed to obtain the grouting material.
[0047] Comparative Examples 2-5
[0048] The difference between Comparative Examples 2-5 and Example 1 is that the contents of the components in the grouting materials are different, as shown in Table 2 for details.
[0049] Table 2 Grouting material ratio table of comparative examples 2-5
[0050]
[0051]
[0052] Comparative Example 6
[0053] The difference between Comparative Example 6 and Example 1 is that the amount of sodium laurate used is 1.1 parts.
[0054] Comparative Example 7
[0055] The difference between Comparative Example 7 and Example 1 is that the amount of sodium laurate used is 1.7 parts.
[0056] Performance Testing
[0057] The cement products obtained in the embodiments and comparative examples were tested for performance. Specifically, the grouting materials and sand in the comparative examples and embodiments were mixed, poured into a regular mold after mixing evenly, and naturally cured for 12 hours. The samples were demoulded to obtain the samples, and the performance was tested according to the following method. The sand fineness was medium sand, the fineness modulus was 2.5-2.8, and the mass ratio of water to sand in the grouting material was 1 (120-150): (550-650), specifically, the mass ratio of water to sand in the grouting material was 135:600.
[0058] (1) Compression / flexural strength test: The mechanical test was carried out using the method of concrete mechanical properties test method standard GB / T50081-2002, and the sample size was 40*40*40mm.
[0059] (2) Free expansion rate measurement: A 40*40*160 mortar test block with copper heads embedded at both ends and no external constraints was used. The mold was a detachable cast iron mold. The shrinkage heads were placed in the reserved holes on both sides and the slurry was poured. The measurement was carried out using a comparator. The experimental method was measured in accordance with the "Test Method for Basic Properties of Building Mortar" (JGJ70-2009). The test results are shown in Table 3.
[0060] Table 3 Performance test table of embodiments and comparative examples
[0061]
[0062]
[0063] From the performance tests of the embodiment and comparative example 1, it can be seen that the sample obtained by the grouting material of the embodiment of the present application has better compressive strength than the sample obtained by the conventional grouting material, and both the early strength and the late strength are very excellent, and the setting time is moderate, and the expansion performance is appropriate. This is because the overall formula system of the grouting material of the present application cooperates with each other, especially the use of whisker inducers, whether sodium laurate, lauric acid, or potassium laurate, which will be adsorbed on the MgO surface after deprotonation in the MgO-MgSO4-H2O system. The carboxyl oxygen of the whisker inducer reacts with [(MgOH)(H2O)] + The formation of a stable chelate inhibits the generation of Mg(OH)2, and allows a large number of basic magnesium sulfate whiskers to form through self-assembly. In addition, the appropriate amount of MgOH2 in the system can also stimulate the kaolin and make the grouting material have suitable expansion properties.
[0064] Further analysis of the performance of Examples 1-5, Comparative Example 2 and Comparative Example 6-7 revealed that, first, Comparative Example 2 did not use a whisker inducer. Although the setting time did not change much, both the early strength and the late strength decreased. In addition, the expansion rate changed, which shows that the addition of a whisker inducer is indeed beneficial to improving the performance of the grouting material. However, in combination with Examples 1-5, it was found that the whisker inducer of Examples 1-5, that is, the amount of sodium laurate, continued to increase, and the performance of Example 1-5 did not gradually increase. In fact, the performance of Example 4 was the best; in addition, Comparative Example 6-7 also reflected that when the amount of sodium laurate was 1.1 parts and 1.7 parts, the performance of Comparative Example 6 and Comparative Example 7 decreased a lot. This shows that although the addition of a whisker inducer is beneficial to the performance of the grouting material, the action process of the whisker inducer is complicated, involving whether the final amount of MgOH2 is appropriate, the number and form of basic magnesium sulfate whiskers, the role of each component, and the coordination between each other, etc. Therefore, an appropriate amount of whisker inducer can play an excellent role in the grouting material system of this application.
[0065] In addition, for the grouting material of the present application, in addition to the role of the whisker inducer, the other components are also very important. From the performance of comparative examples 3-5, it can be seen that the dosage of magnesium oxide, magnesium sulfate and kaolin has a great influence on the performance of the grouting material.
[0066] In the grouting material of the present application, the whisker inducer is very important, but at the same time, the coordination between the various components is also very important. Under the comprehensive effect, the grouting material of the present application has excellent early strength performance, and the compressive strength reaches the standard of ultra-high strength sleeve grouting material. At the same time, it has suitable self-expansion performance and moderate setting time.
[0067] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An early strength, high strength and self-expanding sleeve grouting material, characterized in that: The invention is composed of the following components by weight: 300-330 parts of magnesium oxide, 87-120 parts of magnesium sulfate, 25-33 parts of metakaolin, 1.50-1.65 parts of whisker inducer and 120-150 parts of water; the whisker inducer is at least one of sodium laurate, lauric acid and potassium laurate.
2. The early-strength, high-strength and self-expanding sleeve grouting material according to claim 1, characterized in that: The invention is composed of the following components by weight: 300 parts of magnesium oxide, 120 parts of magnesium sulfate, 30 parts of metakaolin, 1.55 parts of whisker inducer and 135 parts of water.
3. The early-strength, high-strength and self-expanding sleeve grouting material according to claim 1, characterized in that: The magnesium oxide is a powder with a particle size between 20 and 80 microns.
4. The early-strength, high-strength and self-expanding sleeve grouting material according to claim 1, characterized in that: The magnesium sulfate is a powder with a particle size between 20 and 80 microns.
5. The early-strength, high-strength and self-expanding sleeve grouting material according to claim 1, characterized in that: The metakaolin is a powder with a particle size between 20 and 80 microns.
6. A method for preparing the early strength, high strength and self-expanding sleeve grouting material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The magnesium oxide, magnesium sulfate, whisker inducer, metakaolin and water are mixed to prepare a slurry with good fluidity to obtain a grouting material.